2016
DOI: 10.1016/j.irfa.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

UK equity mutual fund alphas make a comeback

Abstract: In this study we re-visit the performance of 887 active UK equity mutual funds using a new approach proposed by Angelidis, Giamouridis and Tessaromatis (2013). The authors argue that mutual funds stock selection is driven by the benchmark index, so if the benchmark generates alpha, there will be a bias in interpretation of manager's stock picking ability. In their model, alpha of a fund is adjusted by benchmark's alpha. By applying this method, we eliminate bias inflicted by the persistently negative alphas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…where , − ℎ , is the excess return of a mutual fund i over a benchmark in period t. As in equation 3SMB and HML are size ad value factors from Fama and French (1993) paper and WML is the Carhart (1997) Similarly, coefficients 1 * , 2, * 3, * 4 * represent the difference between a fund's and benchmark's Carhart betas (Angelidis et al, 2013, Mateus et al 2016. If the coefficients 1 * , 2, * 3, * 4 * are different from zero, this means that the mutual fund manager has different exposure to risk factors than the benchmark index.…”
Section: Performance and Ranking Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…where , − ℎ , is the excess return of a mutual fund i over a benchmark in period t. As in equation 3SMB and HML are size ad value factors from Fama and French (1993) paper and WML is the Carhart (1997) Similarly, coefficients 1 * , 2, * 3, * 4 * represent the difference between a fund's and benchmark's Carhart betas (Angelidis et al, 2013, Mateus et al 2016. If the coefficients 1 * , 2, * 3, * 4 * are different from zero, this means that the mutual fund manager has different exposure to risk factors than the benchmark index.…”
Section: Performance and Ranking Methodologymentioning
confidence: 99%
“…Recently, persistent negative alphas are documented in the FTSE 100 Index in the UK (Mateus et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bauer et al [58] performed rolling regressions to test for the stability of some of the asset pricing models, finding evidence that ethical funds do not outperform relative to conventional funds. Mateus et al [59] followed the approach proposed by Angelidis et al [60] for analyzing the performance of a huge set of UK mutual funds. They revealed that both the Fama-French three-factor and the Carhart four-factor models amplified the underperformance of UK equity mutual funds.…”
Section: Methodsmentioning
confidence: 99%
“…Significant non-zero alphas are reported by Matallin-Saez (2007) for a range of US Russell indices, with the highest (Jensen's) alpha of 7.5% recorded for the Russell 2500 Value index for the period 1995-2004. In the UK, persistently negative fourfactor alphas for the FTSE 100 Index are documented by Mateus, Mateus, and Todorovic (2016) for the period 1992-2013. From this, it follows that fund managers claiming to be active, while not deviating much from a benchmark which has a positive alpha, will be classified as skillful, whereas in fact they exhibit no superior performance.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned UK-focused studies apply standard three and four-factor models to measure performance, and do not make adjustments for the presence of non-zero alphas in passive benchmarks. One UK study, which adjusts the standard Carhart alpha for the alpha of the fund's benchmark, is that of Mateus, Mateus and Todorovic (2016). Using the Angelidis, et al (2013) approach, they document that the benchmark-adjusted alphas of UK equity mutual funds are positive, contrary to most of the existing literature on UK mutual fund performance.…”
Section: Introductionmentioning
confidence: 99%